A modified posterior C1/C2 fusion technique for the management of traumatic odontoid type II fractures by using intraoperative spinal navigation: midterm results - Ishak, Basem; Schneider, Till M.; Gimmy, Valerie; Unterberg, Andreas; Kiening, Karl (Journal of orthopaedic trauma, 2018)
Objectives: To assess midterm safety and efficacy of a modified Goel-Harms technique for the treatment of odontoid instabilities. - Design: Longitudinal prospective cohort study. - Setting: Urban Level 1 Trauma Center in Southwest Germany. - Patients/Participants: Orthopaedic and neurosurgical trauma patients older than 18 years admitted for ≤24 hours. - Main Outcome Measurements: The outcome was evaluated with respect to neurological outcome, radiological outcome and surgical complications. For the functional assessment, the EQ-5D questionnaire was used. Furthermore, the Neck Disability Index and visual analog scale for neck pain were determined. A median follow-up of 39 months (range: 6-97 months) was given. - Results: Of the total sample (n = 56), 26 patients with an acute traumatic odontoid fracture type II underwent posterior atlantoaxial instrumentation using spinal navigation. Neck pain evaluated with visual analog scale and Neck Disability Index showed a significant decrease at final follow-up compared to preoperative values (P < 0.05). According to the EQ-5D, the valuation of quality of life after C1/C2 fusion showed an excellent outcome with complete recovery in most cases (0.7-1). - Conclusions: Our results demonstrate satisfactory and maintained midterm clinical and radiological results after a median follow-up of 39 months. With the use of intraoperative spinal navigation, we demonstrate a modified C1/C2 posterior fusion technique, rendering accuracy, feasibility, and overall safety. - Level of Evidence: Therapeutic Level IV. See Instructions for Authors for a complete description of levels of evidence.
Gesehen am 19.02.2020